FEATURES HAEMOCIRCULATION IN FETOPLACENTAL COMPLEX IN PREECLAMPSIA - Makarov, O.G. (World of Medicine and Biology, 2015)
Ultrasonographic studies were conducted with the definition of systolic diastolic ratio, pulse index and resistance index of uterine artery, uterine spiral arteries, the arteries of the umbilical cord and fetal middle cerebral artery in 30 healthy pregnant women and 90 pregnant women with preeclampsia varying severity. It is shown that as the worsening of pre-eclampsia occurs progressive deterioration of utero-placental-fetal circulation, the most Sensitive indicator of which is the increase in resistance index in the test vessels.